(untitled) (Research, Society and Development, 2022)
The text started from a dialogue with the indigenous leader of the Sateré-Mawé people, from the Andirá-Marau Indigenous Land, located in the Central Amazon, amidst the first and second wave of spread of the new coronavirus in Brazil, and especially in the northern states of the country. The objective was to explore and describe the Sateré-Mawé’s interpretations of the pandemic and identify their strategies to fight the virus. The approach method was qualitative, with descriptive and informational purpose, considering the narrative’s interpretative content. Results showed the existence of specific mitigation strategies to covid-19 by the Sateré-Mawé from Andirá-Marau, despite the ineffectiveness of the Brazilian State, which made clear the autonomy and decision-making power of these native Amazonian peoples.